Internalizing Moral Values through Islamic Podcasts: A Phenomenological Study of Character Education in Secondary Schools - Qurrotul Aien; Nur Aisyah (JURNAL ISLAM NUSANTARA, 2025)
The rapid expansion of digital media presents both challenges and opportunities for character education at the secondary school level. Among emerging digital platforms, Islamic podcasts offer unique potential to deliver moral messages in a reflective, context-specific manner. This study aims to analyze the process of internalizing moral values through Islamic podcast media in secondary school character education. Using a phenomenological approach, the research involved Islamic Religious Education teachers and students. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using phenomenological techniques comprising data reduction, data display, and the identification of essential meanings. The findings indicate that moral value internalization occurs through three stages: value comprehension, value reflection, and value habituation. Islamic podcasts effectively promote honesty, responsibility, and politeness through narrative and experiential content. The medium engages students’ cognitive, affective, and behavioral dimensions in moral learning. Podcasts also create a personal and meaningful learning atmosphere that enhances moral awareness and emotional involvement. Teachers play a crucial role as facilitators and moral role models in guiding the internalization process. This study contributes to character education scholarship by highlighting students’ lived experiences in digital moral learning. It recommends integrating Islamic podcasts as an alternative medium for strengthening character education in secondary schools.